Associação dos indicadores socioeconômicos, fatores pre e perinatais na ocorrência de defeitos de desenvolvimento de esmalte na dentição decídua: estudo de base populacional - Bertha Angelica Chavez Gonzalez (2015)
The developmental defects of enamel (DDE) are common changes in the primary dentition and may be associated with complications in the pre, peri and post-natal care as well as with socioeconomic indicators. Literature is scarce in scientific evidence in population base, once the majority of studies are mainly performed with specific samples. The aim of this cross-sectional study was to estimate the prevalence of DDE in five years old children and the association with premature, complications during pregnancy birth weight and socioeconomic indicators (family income, maternal education, type of preschool attended by children). A cross-sectional study was conducted with a representative sample of 1350 children of five years old of Belo Horizonte - MG. Brazil. After parental consent, children were examined for the diagnosis of DDE using DDE index modificated (FDI, 1992), and through a questionnaire mothers provided socioeconomic data, birth weight and premature and complications during pregnancy. Data analysis was performed using SPSS for Windows 19.0, and included frequency distribution, chi- square test and Fisher's exact test and Poisson regression with robust variance (p < 0.05). The prevalence of DDE was 40.6 %. The demarcated opacity was the most common type of defect (22.7%) by bi-variate analysis; there was also a statistically significant association between developmental defects of enamel and gender, weight birth, complications during pregnancy (Arterial hypertension), mother´s age in the pregnancy, maternal education, type of school of children. The Poisson regression model adjusted showed that there was a higher prevalence of enamel defects among male children (PR: 1.177, 95% CI 1.033 to 1.342), low weight (PR: 1.387, 95% CI 1.61 to 1.656) and very low (PR: 1.667, 95% CI: 1.150 to 2.416). Out of these results it is concluded that the development of enamel defects were more common among male children with low or very low birth weight.